SOEP Innovation Sample (SOEP-IS): Description, structure and documentation - David Richter; Jürgen Schupp (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
The SOEP Group currently is preparing in addition to increasing the size of the core SOEP, to establish a new Innovation Sample (SOEP-IS). This will be established for the period 2012 to 2017 (with a cumulative number of presumably N=5,000 households). Now, in the year 2012, a new subsample is being added for SOEP IS that will also replace the previous SOEP pretest sample. Starting with the 2013 survey, the SOEP will determine the contents of SOEP IS through a competitive refereed application process for the best research questions and their operationalizations, and will distribute the SOEP-IS data as part of its regular data releases.
Keywords: 330